Public Sector Accounting Reforms and Accountability in Government Financial Management in Akwa Ibom State Government - Friday Uke Akam (INTERNATIONAL JOURNAL OF ECONOMICS AND FINANCIAL MANAGEMENT, 2026)
This study examined Public Sector Accounting Reforms and Accountability in Government Financial Management: A Study of Akwa Ibom State Government. The study was motivated by the need to improve transparency, efficiency, and accountability in the management of public funds through modern accounting reforms. Specifically, the study investigated the influence of International Public Sector Accounting Standards (IPSAS) implementation, Integrated Financial Management Information System (IFMIS), accrual accounting reforms, and financial reporting transparency reforms on accountability in government financial management. The study adopted a survey research design, and data were collected through a structured questionnaire administered to 148 respondents drawn from relevant ministries, departments, and agencies in Akwa Ibom State. The data were analyzed using descriptive statistics such as mean and standard deviation, while the hypotheses were tested using the t-test statistical technique at 0.05 level of significance. The findings revealed that IPSAS implementation has a significant influence on accountability in government financial management. The study also found that IFMIS significantly enhances accountability through improved transparency and real-time monitoring of public funds. Furthermore, accrual accounting reforms were found to significantly influence accountability by improving the accuracy and completeness of financial reporting. In addition, financial reporting transparency reforms were shown to have a significant effect on accountability by strengthening oversight and reducing financial mismanagement. The study concluded that public sector accounting reforms play a vital role in strengthening accountability in government financial management in Akwa Ibom State. It was recommended that government should strengthen the implementation of IPSAS, fully adopt IFMIS, enhance accrual accounting practices, and improve financial reporting transparency to ensure effective management of public funds and promote good governance.